Combined Selective Cerebral Hypothermia and Mechanical Artery Recanalization in Acute Ischemic Stroke: In Vitro Study of Cooling Performance - Cattaneo, G.; Schumacher, M.; Wolfertz, J.; Jost, T.; Meckel, S. (American Journal of Neuroradiology, 2015)
BACKGROUND AND PURPOSE: Therapeutic hypothermia represents a promising neuroprotective treatment for patients with ischemic stroke. Selective, intracarotid blood cooling may initiate rapid and early brain hypothermia, reduce systemic effects, and allow combined endovascular mechanical thrombectomy. For this approach, a balloon cooling catheter system was designed and studied in vitro to optimize its cooling performance.MATERIALS AND METHODS: Computational fluid dynamics of blood cooling was performed within the common carotid artery lumen by using 3 different catheter designs (1-, 2-, and 4-balloon array). On the basis of these results, a first catheter prototype was manufactured, and its heat-exchange performance was tested in an artificial in vitro circulation simulating the common carotid artery lumen at different flow rates (inflow temperature of 37°C).RESULTS: In the computational fluid dynamics model, the catheter with the 4-balloon array achieved the highest cooling rate of −1.6°C, which may be attributed to disruption of the thermal boundary layers. In the in vitro study, cooling of the blood substitute at flow rates of 400 mL/min (normal common carotid artery flow) and 250 mL/min (reduced common carotid artery flow due to distal MCA occlusion) achieved a temperature drop inside the blood substitute along the cooling balloons of −1.6°C and −2.2°C, respectively.CONCLUSIONS: The feasibility of intracarotid blood cooling using a new catheter system was demonstrated in vitro. A serial 4-balloon array led to an optimized cooling capacity approaching optimum target temperatures of mild therapeutic hypothermia. To determine the therapeutic efficacy of combined selective therapeutic hypothermia and mechanical thrombectomy, further in vivo studies by using a model of temporary ischemia with large-vessel occlusion and recanalization are required.CCAcommon carotid arteryMTmechanical thrombectomyTHtherapeutic hypothermia